From the Imaginary to Theory of the Gaze in Lacan - Licitra Rosa, Carmelo; Antonucci, Carla; Siracusano, Alberto; Centonze, Diego (Frontiers in Psychology, 2021)
To understand Lacan's thinking process on vision, the entirety of his teaching must be taken into consideration. Until the sixties, the visual field is the imaginary, the constitutive principle of reality in its phenomenal giving to the experience of a subject. This register is the opposite of the field of the speech with the L schema, and subsequently as subordinated to the symbolic system according to the model of the optical schema of the inverted flower vase of Bouasse. It is only with the 1964 seminar that Lacan makes a daring turnaround through which the visual becomes a sign of the emergence of a real that is irreducible both to reality and to the mediation of the subject of knowledge. The split between reality and the real is reproduced in Lacan within the visual field: which is on the one hand the cardinal principle of the consistency of the experience of reality (as imaginary), while on the other it is an element of irreducibility to reality (as object-gaze). This produces a cascade of consequences, first of all the modification of the presentation of the mirror stage. Unlike the voice which, through prosody, tone and volume, finds some strips to anchor itself imaginatively to reality, the gaze, invisible and elusive, escapes the imaginary grasp. Captured in myths, it reveals its power and ability to annihilate - as in the myth of Medusa's gaze - or to make people fall in love, but only with a narcissistic love that leads inexorably to death, as in the myth of Narcissus. The gaze is elusive because the subject is dependent on it in the field of desire. Like the voice, it is about the desire on which the subject is supported, one of the objects on which the phantom depends. In our opinion, thanks to this characteristic, the gaze object can make remote psychoanalytic treatment possible, through easily accessible videoconferencing tools, but at the same time creates new conditions within it that should be carefully evaluated in order to understand its implications in the session itself.